2019
DOI: 10.1186/s13012-019-0900-8
|View full text |Cite
|
Sign up to set email alerts
|

Attributes of context relevant to healthcare professionals’ use of research evidence in clinical practice: a multi-study analysis

Abstract: Background To increase the likelihood of successful implementation of evidence-based practices, researchers, knowledge users, and healthcare professionals must consider aspects of context that promote and hinder implementation in their setting. The purpose of the current study was to identify contextual attributes and their features relevant to implementation by healthcare professionals and compare and contrast these attributes and features across different clinical settings and healthcare profess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 31 publications
0
67
0
Order By: Relevance
“…Our results can also be compared to a multi-study analysis investigating attributes of context found relevant by HCPs in the implementation of evidence-based practices [ 13 ]. The main theme of our study was also found as one of several core contextual factors in this secondary analysis of 145 interviews from 11 studies in different clinical contexts (not including oncology) [ 13 ]. That study also revealed that regulatory and legislative standards were less commonly described attributes that varied in their relevance across clinical contexts [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results can also be compared to a multi-study analysis investigating attributes of context found relevant by HCPs in the implementation of evidence-based practices [ 13 ]. The main theme of our study was also found as one of several core contextual factors in this secondary analysis of 145 interviews from 11 studies in different clinical contexts (not including oncology) [ 13 ]. That study also revealed that regulatory and legislative standards were less commonly described attributes that varied in their relevance across clinical contexts [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study generally highlights the need to further investigate outer setting variables in implementation studies. In order to do so, it is necessary to develop further tools to measure those variables [ 13 ] and to distinguish between modifiable and unmodifiable variables [ 49 ]. Last, but not least, future research on treatment decision making processes should further investigate the role of treatment costs and financial toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Testing and providing views on the validity of the framework A total of 102 (28%) articles described testing or validating PARIHS, or provided comments on the validity of or parts of the framework with a focus on: ▪ The validity of the whole framework (e.g., [24,74,157,195,209]) ▪ The validity of context (e.g., [155,190,280,287,308]) ▪ The validity of facilitation (e.g., [23,58,182,206]) ▪ The validity of evidence (e.g., [255]) ▪ Identifying gaps in the framework (e.g., [64,170,326]) Over the review study period (1998 to 2019), among empirical studies, there was a shift from primarily studying the context element of the framework to more articles evaluating the whole framework. This was also evident in the pattern found in the protocols, which mostly focused on testing facilitation (e.g., [58,182,206]).…”
Section: The Application Of Parihs In Any Other Waymentioning
confidence: 99%
“…The final type of complexity is context-specificity, the tendency for a program's effectiveness to vary based on context [17]. Programs that are successful in some region or population may perform poorly when adopted elsewhere.…”
Section: The Three Types Of Complexitymentioning
confidence: 99%